Lepton transverse polarization in the B→Dlvl decay due to the electromagnetic final state interaction - Braguta, V. V.; Chalov, A. E.; Likhoded, A. A. [UNESP] (American Physical Society (APS), 2002)
The effect of lepton transverse polarization in B0 → D - l+ νl, B+ → D̄0 l+ νl decays (l = τ,μ) is analyzed within the framework of the standard model in the leading order of heavy quark effective theory. It is shown that a nonzero transverse polarization appears due to the electromagnetic final state interaction. The diagrams with intermediate D,D* mesons contributing to the nonvanishing PT are considered. Regarding only the contribution of these mesons, the values of the τ-lepton transverse polarization averaged over the physical region in the B0 → D- τ+ νl, and B+ → D̄0 τ+ νl, decays are equal to 2.60×10-3 and - 1.59×10-3, respectively. In the case of muon decay modes the values of 〈P T〉 are equal to 2.97×10-4 and -6.79×10-4. © 2002 The American Physical Society.